Evaluation of setting kinetics, mechanical strength, ion release, and cytotoxicity of high-strength glass ionomer cement contained elastomeric micelles - Nitchakarn Leenutaphong; Prathip Phantumvanit; Anne M. Young; Piyaphong Panpisut (BMC, 2024)
Abstract Background Low mechanical properties are the main limitation of glass ionomer cements (GICs). The incorporation of elastomeric micelles is expected to enhance the strength of GICs without detrimentally affecting their physical properties and biocompatibility. This study compared the chemical and mechanical properties, as well as the cytotoxicity, of elastomeric micelles-containing glass ionomer cement (DeltaFil, DT) with commonly used materials, including EQUIA Forte Fil (EF), Fuji IX GP Extra (F9), and Ketac Molar (KT). Method Powder particles of GICs were examined with SEM-EDX. Setting kinetics were assessed using ATR-FTIR. Biaxial flexural strength/modulus and Vickers surface microhardness were measured after immersion in water for 24 h and 4 weeks. The release of F, Al, Sr, and P in water over 8 weeks was analyzed using a fluoride-specific electrode and ICP-OES. The toxicity of the material extract on mouse fibroblasts was also evaluated. Results High fluoride levels in the powder were detected with EF and F9. DT demonstrated an initial delay followed by a faster acid reaction compared to other cements, suggesting an improved snap set. DT also exhibited superior flexural strength than other materials at both 24 h and 4 weeks but lower surface microhardness (p < 0.05). EF and F9 showed higher release of F, Al, and P than DT and KT. There was no statistically significant difference in fibroblast viability among the tested materials (p > 0.05). Conclusions Elastomeric micelles-containing glass ionomer cement (DT) exhibited satisfactory mechanical properties and cytocompatibility compared with other materials. DT could, therefore, potentially be considered an alternative high-strength GIC for load-bearing restorations.